Environment and its impact on the collection of linguistic science queens: Read at the forefront of the Ibn Khaldun T 808 H - العاني, لمى فائق (Al-Adab Journal, 2019)
Often Ibn Khaldun reminds one of the most prominent Arab mentality that I have read history, sociology, culture, politics and linked them in an objective and realistic raises controversy and questions, and probably do not agree with his views, particularly what was said among the Arabs, but the scientific method requires that refers to those who have the Siq in the study of social reality in all Matherath Our concern is with respect to the language or (linguistic property), and the most prominent linguistics fields (sociolinguistics), one of the most linguistic studies and realistic is the son of the environment, and the photographer's real relationship with the language at all levels of human groups have found it very evident at the front of the Ibn Khaldun.Hoping thatI have been ableto understand anddisplayedfor the benefit ofthe reader.